Diversity and abundance of water birds in a subarctic lake during three decades - Klemetsen, Anders; Knudsen, Rune (Fauna norvegica, 2013)
The numbers of divers, ducks, gulls, terns and waders in the 15 km2 oligotrophic lake Takvatn, North Norway, were estimated six times during 1983-2012. Systematic mapping surveys were done by boat within the first week after the ice-break in June. Twenty-one species were observed over the years and 12 were regarded as breeding on the lake. Red-breasted merganser Mergus serrator was the dominant diving bird, with the estimated minimum number of breeding pairs varying from 15 to 39 among the years. Black-throated diver Gavia arctica (1-3 pairs), tufted duck Aythya fuligula (2-15 pairs) and common scoter Melanitta nigra (1-5 pairs) bred regularly, while velvet scoter Melanitta fusca (1-2) and goldeneye Bucephala clangula (2-4) were found in some years and mallard Anas platyrhynchos (1 pair) and wigeon Anas penelope (1 pair) in one year. Common gull Larus canus (6-30 pairs) and arctic tern Sterna paradisaea (2-35 pairs) bred in all years. Common sandpiper Tringa hypoleucos (3-9 pairs) and redshank Tringa totanus (1-4 pairs) were regular waders. Density variations of mergansers, gulls and terns are possibly related to density variations of threespine stickleback Gasterosteus aculeatus, their dominant fish prey. As predators and parasite hosts, the water birds are important links in the food web of the lake.